A high-elasticity resin-based cementing material direct tensile test mold and test method
Patent Information
- Application Number
- CN202311818039.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-26
AI Technical Summary
但对于高弹树脂类胶结料试件,在拉伸试验过程中使用这个假定与客观试验观察到的现象不一致,所计算出的真实应力及真实应变会偏大
[0023] 1. The mold provided by the present invention has an arc surface that bulges outward toward the center of the specimen. Then, there will be concave arc surfaces on both sides of the specimen, which will form a stress concentration area, causing the specimen to break at this point during the tensile process, thus improving the reliability of the test.
Smart Images

Figure CN117949301B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high elastic resin tensile testing technology, and relates to a mold and testing method for direct tensile testing of high elastic resin binders. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Polyurethane, epoxy resin, and other resin-based materials, as high-performance binders, have been studied and applied in permeable pavements, bridge deck paving, and colored pavements, demonstrating good road performance. Direct tensile testing is the most direct and effective method for obtaining the mechanical properties of pavement materials. However, there are no unified standards, test molds, or methods for direct tensile testing of resin-based materials. The "Test Method for the Properties of Resin Castings" (GB / T 2567-2021) specifies that the "dumbbell-shaped" specimen for tensile testing should be 200–220 mm in length and 4.0 ± 0.2 mm in thickness. The "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber" (GB / T528-2009) specifies five different specimen sizes: Type 1, Type 1A, Type 2, Type 3, and Type 4. The American standard ASTM D638-14 also specifies five different specimen sizes. The Type IV specimen has the same dimensions as the Type 1 specimen in GB / T 528-2009, with a length of 115 mm and a thickness of 2 mm.
[0004] Direct tensile testing is performed on a tensile testing machine, and the tensile rate varies depending on the specification. GB / T2567-2021 specifies a test speed of 10 mm / min for tensile strength testing; GB / T 528-2009 specifies a tensile rate of 500 mm / min for types 1, 2, and 1A specimens, and 200 mm / min for types 3 and 4; ASTM D638-14 specifies tensile rates ranging from 1 to 500 mm / min for different specimens. For high-elasticity resin binders, different tensile rates will lead to different test results. Under the same test conditions, a lower tensile rate may not cause the specimen to crack. The method for calculating tensile strength is the same in all three specifications: the maximum force recorded during the tensile test is divided by the cross-sectional area at the center of the specimen.
[0005] During tensile testing, stress concentration occurs in the middle section of the specimen, ultimately leading to failure. However, current standards ensure that the middle region of the specimen has a uniform volume and shape, resulting in uniform stress distribution. For some highly elastic resin materials, this can lead to failure to break, making it impossible to accurately evaluate their mechanical properties. Furthermore, the tensile stress in this area is consistent, and stress concentration during the test can occur anywhere within the middle region, leading to significant variability in the test results. Additionally, when highly elastic resin binders break, a large portion of the material is often in a slender state. Using the original specimen's cross-sectional area for calculations in this case results in a significant discrepancy between the calculated results and the actual stress and strain at the fracture point.
[0006] Existing methods for calculating true stress-to-true strain assume that only a 3mm region in the middle of the specimen participates in deformation and that the volume of this region remains constant during tensile testing. The cross-sectional area and deformation length of the middle region at different times can be obtained from the overall displacement of the specimen, allowing the calculation of the true stress-to-true strain curve based on the force-displacement curve. However, for high-elasticity resin-based binder specimens, this assumption during tensile testing is inconsistent with objective experimental observations, leading to overestimation of the calculated true stress and strain. Summary of the Invention
[0007] In order to overcome the shortcomings of the prior art, the purpose of this invention is to provide a direct tensile test mold and test method for high elastic resin binders, which is suitable for evaluating the mechanical properties of high elastic resin binders.
[0008] To achieve the above objectives, the technical solution of the present invention includes:
[0009] In the first aspect, a mold for direct tensile testing of a high-elasticity resin-based binder includes a bottom mold, side molds, and a pull ring;
[0010] The bottom mold includes a forming bottom surface, which is used to form the bottom surface of the tensile specimen;
[0011] The side mold includes a left side mold and a right side mold, which are mounted on the bottom mold and used to shape the left and right sides of the tensile specimen. The contact surfaces between the left side mold and the right side mold and the tensile specimen are the shaped left side and the shaped right side, respectively. The shaped left side and the shaped right side are provided with opposing arc surfaces.
[0012] The pull ring is installed between the two side molds and is integrated with the upper and lower ends of the tensile specimen during the preparation of the tensile specimen.
[0013] Secondly, the method for preparing the tensile specimen of the above-mentioned high-elasticity resin binder direct tensile test mold includes the following steps:
[0014] S1. Slide the side mold into the bottom mold from both sides, so that the left and right arc surfaces are separated by a set distance;
[0015] S2. Place the two pull rings symmetrically at both ends of the space between the side molds;
[0016] S3. Cast the resin binder into a mold to form a test specimen;
[0017] S4. After the specimen has been cured and molded, it is demolded to obtain a tensile specimen with a pull ring at the top.
[0018] Thirdly, the tensile testing method and data conversion method for the above-mentioned tensile specimens include the following steps:
[0019] S5. Perform the tensile test on the tensile testing machine until the specimen breaks at the concave arc surface.
[0020] S6. Determine the part L0 of the high-elastic resin binder specimen that participates in deformation during the test on the two opposing arc surfaces of the left and right molds.
[0021] S7. Based on the length L0 involved in deformation in the middle of the specimen, convert it into a true stress-strain curve that conforms to the characteristics of high-elasticity resin binders; then calculate the area of this curve to obtain the fracture energy density.
[0022] The beneficial effects of this invention are as follows:
[0023] 1. The mold provided by the present invention has an arc surface that bulges outward toward the center of the specimen. Then, there will be concave arc surfaces on both sides of the specimen, which will form a stress concentration area, causing the specimen to break at this point during the tensile process, thus improving the reliability of the test.
[0024] 2. This invention proposes a novel method for calculating the true stress-true strain based on the characteristics of high-elasticity resin binders and the features of the developed mold. The force-displacement curve obtained from conventional tests is transformed into a true stress-true strain curve for the central region of the specimen, and the fracture energy density is calculated using this curve. This method not only accurately reflects the stress state of the specimen but also better reflects the mechanical characteristics of the binder, enabling accurate evaluation of the performance of different resin binders. Attached Figure Description
[0025] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0026] Figure 1 This is a schematic diagram of the bottom mold in a specific embodiment of the present invention;
[0027] Figure 2This is a schematic diagram of the pull ring structure in a specific embodiment of the present invention;
[0028] Figure 3 This is a schematic diagram of the side mold structure in a specific embodiment of the present invention;
[0029] Figure 4 This is a schematic diagram of the installation of the test mold in a specific embodiment of the present invention;
[0030] Figure 5 This is a schematic diagram of the distance L0 between the midpoints of the curves on both sides of the midpoint of the middle circular curve of the side mold in an embodiment of the present invention;
[0031] Figure 6 The following are fracture energy density diagrams of various materials using the new conversion method in this embodiment of the invention;
[0032] Figure 7 This is a graph showing the true stress-strain curve calculated by the new conversion method for PRM-modified asphalt in this embodiment of the invention.
[0033] Figure 8 This is a graph showing the true stress-true strain curve calculated by the new conversion method for rubber-modified asphalt in this embodiment of the invention.
[0034] Figure 9 This is a graph showing the true stress-strain curve calculated using the new conversion method for 70# base asphalt in this embodiment of the invention.
[0035] Figure 10 This is a graph showing the true stress-strain curve calculated by the new conversion method for SBS IC modified asphalt in this embodiment of the invention.
[0036] Figure 11 This is a graph showing the true stress-strain curve calculated by the new conversion method for high-viscosity modified asphalt in this embodiment of the invention.
[0037] Figure 12 This is the true stress-true strain curve calculated by the new conversion method for BR-PUA binder after 1 day of curing in this embodiment of the invention.
[0038] Figure 13 This is the true stress-true strain curve calculated by the new conversion method for BR-PUA binder after 3 days of curing in this embodiment of the invention.
[0039] Figure 14 This is the force-displacement curve of the BR-PUA binder after curing for 1 day in Comparative Example 1 of this invention, obtained by conventional tensile testing.
[0040] Figure 15 The fracture energy density diagram of the material selected in Comparative Example 2 of this invention is based on the existing real stress-real strain calculation method.
[0041] Figure 16 The actual stress-strain curve is calculated using the existing conversion method for PRM-modified asphalt in Comparative Example 2 of this invention.
[0042] Figure 17 The image shows the actual stress-strain curve calculated using the existing conversion method for rubber-modified asphalt in Comparative Example 2 of this invention.
[0043] Figure 18 This is a graph showing the actual stress-strain curve of 70# base asphalt calculated using the existing conversion method in Comparative Example 2 of this invention.
[0044] Figure 19 This is a graph showing the actual stress-strain curve calculated using the existing conversion method for SBS IC modified asphalt in Comparative Example 2 of this invention.
[0045] Figure 20 The actual stress-strain curve of high-viscosity modified asphalt calculated by the existing conversion method in Comparative Example 2 of this invention is shown.
[0046] Figure 21 This is the actual stress-strain curve of the BR-PUA binder after 1 day of curing in Comparative Example 2 of this invention, calculated using the existing conversion method.
[0047] Figure 22 This is the actual stress-strain curve calculated using the existing conversion method for the BR-PUA binder after 3 days of curing in Comparative Example 2 of this invention.
[0048] In the diagram: 1. Bottom mold; 2. Left side mold; 3. Right side mold; 4. Pull ring; 5. Stretch hole. Detailed Implementation
[0049] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0050] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0051] Example 1
[0052] This embodiment provides a mold for direct tensile testing of high-elasticity resin-based binders, including a bottom mold, side molds, and a pull ring;
[0053] like Figure 1 As shown, the bottom mold 1 includes a forming bottom surface, which is used to form the bottom surface of the tensile specimen;
[0054] like Figure 2 As shown, the side mold includes a left mold 2 and a right mold 3. The left mold 2 and the right mold 3 are installed on the bottom mold 1 and are used to shape the left and right sides of the tensile specimen. The contact surfaces of the left mold 2 and the right mold 3 with the tensile specimen are the left side and the right side, respectively. The left side and the right side are provided with opposing protruding left arc surfaces and right arc surfaces.
[0055] The pull ring 4 is installed between the two side dies and is integrated with the upper and lower ends of the tensile specimen during the preparation of the tensile specimen, such as... Figure 3 As shown, there are stretching holes 5 at the left and right symmetrical axes of the pull ring.
[0056] Optional, such as Figure 4 As shown, the bottom and upper ends of the bottom surface of the bottom mold 1 have strip-shaped protrusions that are higher than the bottom surface of the bottom mold, which serve as tracks for the left mold 2 and the right mold 3 to slide into, and constrain the relative positions of the left mold 2 and the right mold 3 on the bottom mold 1.
[0057] Optionally, pull ring 4 includes an upper pull ring and a lower pull ring, such as Figure 4 As shown, the upper and lower pull rings have the same shape and are installed in a symmetrical manner.
[0058] Optionally, the positions of the left and right arc surfaces are symmetrical with respect to the left and right axes of symmetry of the specimen.
[0059] This design creates a concave area on both sides in the middle of the cast tensile specimen. This area has the lowest cross-sectional area, resulting in the highest tensile stress during tensioning and making the specimen more prone to fracture, thus reducing the variability of the test. Because the cross-sectional area here is small enough, combined with a faster tensile speed, it can be quickly broken, preventing excessive deformation without the specimen breaking.
[0060] Optional, such as Figure 5 As shown, the left and right arc surfaces are each composed of two circular curves with a radius of 7.04 mm and a length of 8.48 mm (i.e., two circular curves form a single arc surface, and the two circular curves are connected by a straight line); the width of the upper and lower pull rings is 20 mm; the distance between the upper and lower pull rings is 40.1 mm.
[0061] After the left and right arc surfaces are installed, the minimum distance between them is 2mm.
[0062] Optionally, a release agent may be applied to the contact surface between the side mold and the specimen.
[0063] The release agent is composed of 2 ± 0.2 parts by weight of glycerin and 1 ± 0.2 parts by weight of talc, which facilitates demolding of the specimen.
[0064] Optionally, an anti-stick film is laid on the surface of the bottom mold 1 that contacts the specimen and the surface of the bottom mold 1 that contacts the left mold 2 / right mold 3;
[0065] Optionally, no anti-stick film is laid at the contact position between the pull ring 4 and the specimen.
[0066] Optionally, the anti-stick film is a polytetrafluoroethylene film.
[0067] Instead of using a release agent to separate the bottom mold 1 from the left mold 2 / right mold 3, an anti-stick film is used. This is because during the process of the side molds moving inward until they are completely separated from the bottom mold 1, the bottom of the specimen will experience significant friction with the bottom mold. If the release agent is insufficiently or unevenly applied, or if the specimen is brittle, it will make it difficult to demold the specimen or even damage it. The polytetrafluoroethylene film can ensure that the film thickness is uniform at all locations and will not thin during the friction process.
[0068] Optionally, the corners of the pull ring 4 are rounded; since the pull ring 4 is directly bonded to the specimen, stress concentration at the interface between the sharp corners and the adhesive is prevented, thus avoiding affecting the normal conduct of the test.
[0069] Example 2
[0070] This embodiment provides a method for preparing a tensile specimen using a direct tensile testing mold for a high-elasticity resin binder as described in Embodiment 1, comprising the following steps:
[0071] S1. Slide the two side molds into the bottom mold from both sides, so that the left and right arc surfaces are separated by a set distance;
[0072] S2. Place the two pull rings symmetrically at both ends of the space between the two side molds;
[0073] S3. Mix the resin binder evenly, and quickly cast the specimen into the mold before the binder loses its fluidity.
[0074] S4. After the specimen is cured and formed, demold it. When demolding, push both side molds outwards towards one side mold at the same time until the two side molds and the middle specimen are completely separated from the bottom mold 1. Then remove the two side molds to obtain a tensile specimen with a pull ring at the top.
[0075] Optionally, in S1, an anti-stick film is laid on the contact surface between the side mold and the bottom mold; the anti-stick film is a polytetrafluoroethylene film.
[0076] Optionally, in S1, a release agent is applied to the contact surface between the side mold and the specimen. The release agent is composed of a mixture of 2 ± 0.2 parts by weight of glycerin and 1 ± 0.2 parts by weight of talc powder to facilitate demolding of the specimen.
[0077] Optionally, in S2, the rounded corners of the pull ring contact the specimen.
[0078] Optionally, in S3, after casting, a layer of isolation material is covered on the surface of the specimen, and a weight with a flat bottom is placed on top of the isolation material to squeeze out excess binder material; this avoids the binder material from overflowing the side mold and forming large protrusions on the surface of the specimen, which would affect the normal conduct of the test.
[0079] Optionally, in S4, push the two side molds outwards towards the direction of the single side mold, and on the other side, grasp the separator (PTFE film) and move it slowly in the same direction to separate the bottom mold and the side mold; after the bottom mold and the side mold are completely separated, first remove the film, and then press the pull ring to slowly remove the two side molds to avoid damage to the specimen.
[0080] Example 3
[0081] This embodiment provides a direct tensile test and data conversion method for the tensile specimen prepared in Example 2, including the following steps:
[0082] S5. Perform the tensile test on the tensile testing machine until the specimen breaks at the concave arc surface.
[0083] S6. Determine the part L0 of the high-elastic resin binder specimen that participates in deformation during the test on the two opposing arc surfaces of the left and right molds.
[0084] S7. Based on the length L0 involved in deformation in the middle of the specimen, convert it into a true stress-strain curve that conforms to the characteristics of high-elasticity resin binders; then calculate the area of this curve to obtain the fracture energy density.
[0085] Optionally, in S5, when the specimen with the pull ring is installed on the tensile testing machine fixture, the center line of the fixture is made to coincide with the center line of the resin binder in the middle, and the fixture can remain stable during the upward / downward stretching process to avoid the specimen being subjected to eccentric tensile force, which would affect the test results.
[0086] The stretching speed was selected as 500 mm / min. The faster stretching speed can ensure that the high elastic resin material is broken under rapid stretching.
[0087] Optionally, in S6, as described above, the left and right arc surfaces are each composed of two circular curves with a radius of 7.04 mm and a length of 8.48 mm (i.e., two circular curves form a single arc surface, and the two circular curves are connected by a straight line). Figure 5As shown; the contact point between the dashed line and the circular curve with a radius of 7.04 mm is the midpoint of a single circular curve, and the straight-line distance between the midpoints of the two circular curves is L0. The area between the two dashed lines is the part that mainly participates in the deformation. When the sample is prepared using the mold of Example 1, L0 is 8 mm.
[0088] Optionally, in S7, the calculation method for true stress-true strain is as follows:
[0089]
[0090]
[0091] Where, σ t —True stress, MPa;
[0092] F—the force derived—the force at a certain moment in the displacement curve, in N;
[0093] A—the cross-sectional area corresponding to the force at a certain moment;
[0094] ε t —Realistic response;
[0095] L0—The length of the middle part of the specimen that participates in deformation during the test, in mm;
[0096] L—The length of the specimen after deformation at a certain moment during the tensile test, in mm.
[0097] Optionally, in S6 and S7, L is the sum of L0 and the real-time displacement.
[0098] Optionally, in the S7, the tensile testing machine's sensors are quite sensitive. After the specimen breaks, due to minor vibrations within the instrument itself, the sensors will continue to record force and displacement data. The force in this subsequently recorded data is significantly smaller than the force before breakage, therefore this portion of the force-displacement data should be discarded.
[0099] Optionally, in S7, the true stress-true strain curve is plotted, and the fracture energy density is obtained by calculating the area between the curve and the true strain axis using mathematical software.
[0100] The true stress is defined as the ratio of the applied load to the instantaneous cross-sectional area; the true strain is defined as the strain determined considering the reduction in cross-sectional area. Compared with the common force-displacement curve, the converted true stress-true strain curve has a greater correlation with the actual situation of the specimen. The newly developed conversion method conforms to the characteristics of high-elasticity resin binders, and the fracture energy density is calculated based on it. The fracture energy density is defined as the energy per unit volume required to induce fracture of the specimen, which is obtained by the area of the true stress-true strain curve. It reflects the fracture performance of the resin binder throughout the entire test process and is a better measure of the fracture performance of resin binders than the tensile strength of the material at a certain moment in traditional specifications.
[0101] Example 4
[0102] In this embodiment, resin-based binders, 70# base asphalt, SBS IC modified asphalt, PRM high modulus modified asphalt, rubber modified asphalt (80 mesh, 18%), and high viscosity modified asphalt were selected for comparative tests.
[0103] The resin-based binder used is cold-mixed polyurea binder BR-PUA, a commercially available product manufactured by Chengdu Benbang Road & Bridge New Materials Co., Ltd., and its basic properties are shown in Table 1.
[0104] Table 1
[0105]
[0106] The basic properties of various asphalts are shown in Table 2.
[0107] Table 2
[0108]
[0109] Using the mold in Example 1, first place a layer of release film (polytetrafluoroethylene film) on the bottom mold. Then, prepare the release agent according to the ratio of glycerin: talc = 2:1 and apply it to the inner side of the two side molds that are in direct contact with the adhesive. Slowly slide the two side molds into the bottom mold from both sides, being careful not to wrinkle the release agent (polytetrafluoroethylene film). Then, symmetrically place the two pull rings into the areas formed by the two side molds, making sure that the smooth side of the pull ring is in direct contact with the adhesive. Do not apply release agent to the pull rings.
[0110] Mix the resin-based binder or asphalt to be tested evenly according to the manufacturer's recommended ratio or the required ratio, and slowly pour it into the mold, ensuring that the binder slightly exceeds the top of the side mold. Cover the mold with a layer of release material (PTFE film), and then place a weight to evenly distribute the binder on the surface of the specimen. After curing, remove the weight and slowly peel off the release material (PTFE film) to avoid damaging the specimen surface. Push both side molds outwards towards one side while simultaneously grasping the release material (PTFE film) on the other side and moving it to one side to separate the side molds, specimen, and bottom release material (PTFE film) from the bottom mold. Slowly peel off the bottom release material (PTFE film) of the side molds, and then hold the pull ring to slowly remove both side molds, thus obtaining the specimen to be tested. BR-PUA uses two curing times: 1 day and 3 days.
[0111] Place the specimen on the clamp of the tensile testing machine, aligning the centerline of the clamp with the centerline of the resin binder. After installation, perform "zeroing" and set the tensile speed to 500 mm / min before starting the test (after the specimen breaks, the force data recorded by the instrument will drop significantly; discard these data). Add L0 to the displacement data in the force-displacement curve exported from the instrument to obtain the deformation state of the specimen's center at different times, and then calculate the true strain. Assuming that the volume of the deformation area in the middle of the specimen remains constant, the cross-sectional area corresponding to the force at different times can be calculated, thereby calculating the true stress. Finally, the calculated true stress-true strain curve yields the fracture energy density of the tested specimen.
[0112] The calculated fracture energy density of the selected material is as follows: Figure 6 As shown.
[0113] The fracture energy density (MPa) values for each material are as follows: PRM modified asphalt: 0.47805, rubber modified asphalt: 1.19198, 70# base asphalt: 1.95167, SBS IC modified asphalt: 3.61593, high viscosity modified asphalt: 5.10811, BR-PUA binder after 1 day of curing: 7.00204, BR-PUA binder after 3 days of curing: 11.7019.
[0114] The true stress-true strain curve calculated by the new conversion method for PRM modified asphalt is as follows: Figure 7 As shown.
[0115] The true stress-true strain curve calculated by the new conversion method for rubber-modified asphalt is as follows: Figure 8 As shown.
[0116] The true stress-true strain curve calculated using the new conversion method for 70# base asphalt is shown below. Figure 9 As shown.
[0117] The true stress-true strain curve calculated by the new conversion method for SBS IC modified asphalt is as follows: Figure 10 As shown.
[0118] The true stress-true strain curve calculated by the new conversion method for high-viscosity modified asphalt is shown in the figure below. Figure 11 As shown.
[0119] The true stress-true strain curve of BR-PUA binder calculated using the new conversion method after 1 day of curing is shown in the figure below. Figure 12 As shown.
[0120] The true stress-true strain curve of BR-PUA binder calculated using the new conversion method after 3 days of curing is shown in the figure below. Figure 13 As shown.
[0121] Comparative Example 1
[0122] The test was conducted using Type 1 "dumbbell-shaped" specimens for tensile testing as specified in GB / T 528-2009.
[0123] The test procedure is as follows: Prepare a silicone mold with the specimen dimensions specified in GB / T 528-2009 for Type 1 specimens. Mix 2 ± 0.2 parts by weight of glycerin and 1 ± 0.2 parts by weight of talc to form a release agent, and apply it evenly to the inside of the mold. Mix the resin binder to be tested evenly according to the manufacturer's recommended ratio or the required ratio, and slowly pour it into the silicone mold, ensuring the binder slightly exceeds the top and sides of the mold. Cover the mold with a release agent (PTFE film), and then place a weight to evenly distribute the binder on the specimen surface. After curing for 1 day, remove the weight, slowly peel off the release agent (PTFE film) to avoid damaging the specimen surface, and then slowly squeeze the specimen out from the bottom of the silicone mold. The installation and testing procedure for dumbbell-shaped specimens are the same as in Example 4.
[0124] The formula for calculating the tensile strength of a traditional dumbbell-shaped specimen is as follows:
[0125]
[0126] In the formula:
[0127] TS—Tensile strength, MPa;
[0128] F m —The maximum force recorded by the instrument, in N;
[0129] W—Width of the slender middle section of the dumbbell-shaped specimen, 6 mm;
[0130] t—thickness of the slender middle section of the dumbbell-shaped specimen, 2 mm;
[0131] From the above formulas, it can be seen that the principle of calculating tensile strength for traditional dumbbell-shaped specimens is similar to that of calculating true stress. However, it uses the initial cross-sectional area of the specimen, not the cross-sectional area corresponding to the maximum force. This is reasonable for materials with small deformation, but not suitable for materials like resin binders, which have good elasticity and large deformation. Because resin binders have good elasticity, they cannot be broken after the instrument is fully extended. The force-displacement curve for the entire test process is as follows: Figure 14 As shown, the maximum force is 58.4 N, so TS = 4.867 MPa. Compared with the peak stress in the true strain-true stress curve obtained from the direct tensile test of resin after curing for 1 day, the peak stress is relatively small. The traditional dumbbell-shaped specimen and its calculation method cannot truly reflect the mechanical properties of resin binders. However, the fracture energy density calculated by the new mold and new method can truly reflect the mechanical properties of resin binders.
[0132] Comparative Example 2
[0133] The preparation and testing procedures for the materials and specimens in this comparative experiment are consistent with those in the example. The only difference lies in the conversion method for transforming the force-displacement curve into the true stress-strain curve. An existing conversion method is used, assuming that only a 3mm region in the middle of the specimen participates in deformation (L0 = 3), and assuming that the volume of the deformed portion remains constant during the experiment. The force-displacement curve obtained from the experiment is then used to calculate the true stress-strain curve for different materials using formulas, thereby deriving their fracture energy density.
[0134] The fracture energy density of the selected material is based on existing real stress-real strain calculation methods, such as... Figure 15 As shown.
[0135] The fracture energy density (MPa) values for each material are as follows: PRM modified asphalt: 1.82637, rubber modified asphalt: 4.31193, 70# base asphalt: 5.19802, SBS IC modified asphalt: 13.2843, high viscosity modified asphalt: 19.2350, BR-PUA binder after 1 day of curing: 24.7198, BR-PUA binder after 3 days of curing: 42.767.
[0136] The actual stress-strain curve calculated using existing conversion methods for PRM modified asphalt is as follows: Figure 16 As shown.
[0137] The actual stress-strain curve calculated using existing conversion methods for rubber-modified asphalt is as follows: Figure 17 As shown.
[0138] The actual stress-strain curve calculated using the existing conversion method for 70# base asphalt is as follows: Figure 18 As shown.
[0139] The actual stress-strain curve calculated using existing conversion methods for SBS IC modified asphalt is as follows: Figure 19 As shown.
[0140] The actual stress-actual strain curve calculated using existing conversion methods for high-viscosity modified asphalt is shown in the figure below. Figure 20 As shown.
[0141] The actual stress-strain curve of BR-PUA binder calculated using existing conversion methods after 1 day of curing is shown below. Figure 21 As shown.
[0142] The actual stress-strain curve of BR-PUA binder calculated using existing conversion methods after 3 days of curing is shown below. Figure 22 As shown.
[0143] from Figures 16-22 It can be observed that the actual stress and strain values calculated using the existing conversion method are greater than those calculated using the newly developed method. This is because the existing conversion method assumes a smaller volume in the 3mm deformation region compared to the 8mm deformation region assumed in the newly developed method, resulting in a smaller calculated cross-sectional area at the center of the specimen at different times. Under the same force, the actual stress and strain calculated using the existing conversion method will be larger, and the calculated fracture energy density will also increase accordingly. Figure 15 As shown. The existing conversion method for calculating high-elasticity resin binders has a shortcoming: the assumption that only the central 3mm region participates in deformation during the experiment does not conform to the objective experimental phenomena of high-elasticity resin binders, thus resulting in overestimating the calculated true stress, true strain, and fracture energy density. The new conversion method, based on the characteristics of high-elasticity resin binders and the features of the developed mold, defines L0 as the distance between the midpoints of the two circular curves forming the middle arc surface of the side mold. The resulting true stress-strain curve conforms to the objective experimental phenomena of high-elasticity resin binders.
[0144] As can be seen from the differences between the embodiments and comparative examples, the present invention overcomes the shortcomings of the prior art and corrects the stress, strain and fracture energy density results of high-elasticity resin binders.
[0145] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A direct tensile testing mold for high-elastic resin-based binders, characterized in that, Includes bottom mold, side mold, and pull ring; The bottom mold includes a forming bottom surface, which is used to form the bottom surface of the tensile specimen; The side mold includes a left mold and a right mold, which are mounted on the bottom mold and used to shape the left and right sides of the tensile specimen. The contact surfaces between the left mold and the right mold and the tensile specimen are the shaped left and shaped right sides, respectively. Opposing arc surfaces are provided on the shaped left and shaped right sides. The portions of the high-elastic resin binder specimen that participate in deformation during the test are defined on the two opposing arc surfaces of the left and right molds. L 0; The straight-line distance between the midpoints of the two circular curves is L 0 is 8mm; the left and right arc surfaces are each composed of two circular curves with a radius of 7.04mm and a length of 8.48mm, and the minimum distance between the left and right arc surfaces is 2mm; The pull ring is installed between the two side molds and is integrated with the upper and lower ends of the tensile specimen during the preparation of the tensile specimen. An anti-stick film is laid on the surface of the bottom mold that contacts the specimen and the surface of the bottom mold that contacts the left / right mold; the anti-stick film is a polytetrafluoroethylene film; The bottom and upper ends of the bottom surface of the mold have strip-shaped protrusions that are higher than the bottom surface of the mold. These protrusions act as tracks for the left and right molds to slide into, and also constrain the relative positions of the left and right molds on the bottom mold.
2. The direct tensile test mold for high-elastic resin binders as described in claim 1, characterized in that, Pull rings include an upper pull ring and a lower pull ring. The upper and lower pull rings have the same shape and are installed in a symmetrical manner.
3. The direct tensile test mold for high-elastic resin binders as described in claim 1, characterized in that, The positions of the left and right arc surfaces are symmetrical with respect to the left and right axes of symmetry of the specimen.
4. The direct tensile test mold for high-elastic resin binders as described in claim 1, characterized in that, The contact surfaces between the left / right mold and the specimen are coated with a release agent; the release agent is composed of 2 ± 0.2 parts by weight of glycerin and 1 ± 0.2 parts by weight of talc.
5. A method for preparing a tensile specimen based on a direct tensile testing mold for a high-elasticity resin binder as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Slide the two side molds into the bottom mold from both sides, so that the left and right arc surfaces are separated by a set distance; S2. Place the two pull rings symmetrically at both ends of the space between the two side molds; S3. Cast the resin binder into a mold to form a test specimen; S4. After the specimen has been cured and molded, it is demolded to obtain a tensile specimen with a pull ring at the top.
6. The method for preparing a tensile specimen as described in claim 5, characterized in that, In S3, after casting, a layer of isolation material is covered on the surface of the specimen, and a weight with a flat bottom is placed on top of the isolation material to squeeze out excess binder.
7. The method for preparing a tensile specimen as described in claim 5, characterized in that, In S1, an anti-stick film is laid on the contact surface between the side mold and the bottom mold; a release agent is applied to the contact surface between the side mold and the specimen.
8. A method for tensile testing of a tensile specimen, characterized in that, the tensile test... The specimen is prepared by the method for preparing tensile specimens according to any one of claims 5-7; Includes the following steps: S5. Perform the tensile test on the tensile testing machine until the specimen breaks at the concave arc surface. S6. Determine the parts of the high-elastic resin binder specimen that participate in deformation during the test on the two opposing arc surfaces of the left and right molds. ; S7. Based on the length of the middle part of the specimen that participates in deformation. Based on this, the stress-strain curve is converted to conform to the characteristics of high-elasticity resin binders; then the area of this curve is calculated to obtain the fracture energy density. In S6, the left and right arc surfaces are each composed of two circular curves with a radius of 7.04 mm and a length of 8.48 mm. The straight-line distance between the midpoints of the two circular curves is... It is 8mm; In S7, the calculation method for true stress-true strain is as follows: in, —True stress, MPa; —The force derived—the force at a certain moment in the displacement curve, in N; —The cross-sectional area corresponding to the force at a certain moment; —Realistic response; —The length of the specimen's middle section that participated in deformation during the test, in mm; —The length of the specimen after deformation at a certain moment during the tensile test, in mm.
Citation Information
Patent Citations
Biological asphalt fracture energy testing device
CN213903125U